Lactose and milk urea nitrogen: fluctuations during lactation in Holstein cows (2014)
ABSTRACT: The objective of this study was to evaluate lactose and milk urea nitrogen (MUN) in milk from Holstein cows and their relationship with days in milk (DIM), milk yield, milk fat, milk protein, and somatic cell count (SCC). A total of 1,034 records corresponding to morning and afternoon milkings of 148 Holstein cows were used. Records were taken from 16 herds located in the Northern and Eastern dairy regions of Antioquia (Colombia). The curves were fitted using a generalized additive mixed model with smoothed estimates to find the best smoothing intensity factors involved in MUN and lactose concentration. Regarding MUN, the contemporary group effect was highly significant, but the parity effect was not significant. The DIM, lactose and milk fat smoothed covariates were highly significant, while milk yield and fat and SCC showed no statistical difference. Regarding lactose content, the contemporary group effect was highly significant, while the parity effect was not significant. Days in milk, MUN, milk fat, milk protein, and afternoon-milking SCC smoothed covariates were highly significant, while milk yield and morning-milking SCC were not significant. Lactose and milk urea nitrogen concentrations are affected by various factors throughout lactation, mainly by days in milk.